The level of training outsourcing effectiveness towards employee job performance at Naza Talyya Hotel, Melaka / Taufik Tumin - Tumin, Taufik (2014)
Employee is one of the blood stream and key value for organization to develop and growth well. In the development of organizations, training plays a vital role, improving performance as well as increasing productivity of organization. This study was conducted to measure the level of training outsourcing effectiveness and employee job performance in Naza Talyya Hotel, Melaka. The main objective is researcher need to identify the level of employee job performance in Naza Talyya Hotel, Melaka. This study also wants to determine the relationship of availability of training program and employee job performance. Next, this study want to determine the relationship between customization of training program and employee job performance and supervisory support toward training program and job performance. This research focusing in hospitality industry. The study was conducted among 44 respondents in Naza Talyya Hotel, Melaka which is located in Bandaraya Melaka. A correlation analysis will be used to identify the relationship for each independent variable by using mean, frequency and percentage. For findings, the two dimensions show relationship between availability of training and customization of training program towards employee job performance. From the findings justified that availability of training program is the most influence factor that effect employee job performance improvement. The findings also justified Naza Talyya Hotel, Melaka support staff achieve a high level of job performance.